Rural Areas in Poland in The Context of Changes in Population Age Structure in 1996, 2001 and 2006 - Szymańska, Daniela; Biegańska, Jadwiga; Gil, Anna (Bulletin of Geography. Socio-economic Series, 2009)
The article presents changes in the rural age structures in Poland as observed in the years 1996, 2001 and 2006. The changes in population numbers are analysed with respect to age groups, the aging index and the old-age rate. Regarding its spatial scope, the article covers rural areas in Poland and the basic territorial units it uses are rural communes and the rural parts of mixed rural-urban communes that altogether amount to 2,171 units (as of 2006). The obtained results are discussed in a broader context of urban as well as countrywide age structures.